Influence of microstructures on the quality of welding joints / Muhammad Afif Arafat Ramli. - Ramli, Muhammad Afif Arafat (2009)
Fundamentally, the main idea of this subject is to overview the influences of microstructure on the quality of welding joints. This study involves looking at the microstructure for different welded joints and evaluated the quality. In the working of welding, there are various types of welding joint. The microstructure on welded joint is so related to the quality of the welding. The objectives are to learn the basic understanding of the principal of welding and microstructures; to address this issue and try to observe the quality related on microstructure; to determine the transformation of phases during welding; to identify the result from the DT of the specimen produce by welding. Basically, the significance of the proposed project is to reduce the problem occur after the welding process such as crack which is must be avoid To achieve the objective, 3 joints of welding will be held (Butt-Joint, T-Joint, and Lap-Joint). The process for each joint that is used is Gas Metal Arc Welding or MIG. For each joint, there will be 2 specimen with different parameter which are the wire speed, current and voltage. After all the welding process is finished, the specimen will undergo a quality test which is destructive test (DT) and only Butt-Joint that is suitable with this destructive test The quality of other joint is observed with microstructure, this is because the designs of the joint do not meet the requirement. The result of this study is based on the microstructure of each joint which must go through several procedures with the specimen before the microstructure can been observed with the microstructure itself, the size of grain boundaries can show the quality of the design with each joint.